1994
DOI: 10.2307/3578561
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray-Induced Cell Death: Apoptosis and Necrosis

Abstract: X-ray-induced cell death in MOLT-4N1, a subclone of MOLT-4 cells, and M10 cells was studied with respect to their modes of cell death, apoptosis and necrosis. MOLT-4N1 cells showed radiosensitivity similar to that of M10 cells, a radiosensitive mutant of L5178Y, as determined by the colony formation assay. Analysis of cell size demonstrated that MOLT-4N1 cells increased in size at an early stage after irradiation and then decreased to a size smaller than that of control cells, whereas the size of irradiated M1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 21 publications
0
27
1
1
Order By: Relevance
“…These long DNA molecules could be derived from necrosis instead of apoptosis. It has been reported that cell death associated with tissue necrosis may generate longer DNA fragments in addition to the typical oligonucleosomal DNA fragments (42,43). For future studies, it would be interesting to study the DNA methylation profile of these longer DNA molecules to see if they bear resemblances to that expected for the liver.…”
Section: Discussionmentioning
confidence: 99%
“…These long DNA molecules could be derived from necrosis instead of apoptosis. It has been reported that cell death associated with tissue necrosis may generate longer DNA fragments in addition to the typical oligonucleosomal DNA fragments (42,43). For future studies, it would be interesting to study the DNA methylation profile of these longer DNA molecules to see if they bear resemblances to that expected for the liver.…”
Section: Discussionmentioning
confidence: 99%
“…MOLT-4 cells are derived from a human T-cell leukemia, are highly radiosensitive, and die by apoptosis after X-irradiation or hyperthermia (Han et al 1974;Akagi et al 1993;Shinohara and Nakano 1993;Nakano and Shinohara 1994;Nakano et al 1997). They accumulate p53 protein in response to various external stresses such as ionizing radiation or heat (Nakano et al 1997;Inanami et al 1999;Nakano and Shinohara 1999;Zhao et al 1999;Enomoto et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Living cells can actively react to the X-ray induced damage by, e.g., the start of apoptosis [111]. However, for the exposure to radiation doses much lower than the doses applied here, these effects have been shown to occur on time scales of several hours [111], which is long compared to one measurement (well beyond one hour of total scan time). Fig.…”
Section: Radiation Damagementioning
confidence: 99%
“…However, the radiation can also affect other biological molecules in the cell like for instance membrane lipids, which might lead to a disturbance of the membrane function and a loss of compartmentalization [104]. The lethality of mammalian cells upon irradiation has been addressed in various studies [108][109][110][111][112][113]. In most mammalian cell populations, an exposure to a dose of 10 Gy X-rays causes more than 90% cell killing [107].…”
Section: Radiation Damage and Dosementioning
confidence: 99%